Islamic Education Planning at Madrasah Aliyah Nurul Muhajirin Tanjung Lago - Zainal Berlian (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2022)
This article discusses the planning of Islamic education at MA Nurul Muhajirin Tanjung Lago, Banyuasin Regency, South Sumatra Province. In this study, the researcher used a qualitative descriptive study. The techniques used in data analysis are data reduction, data presentation, and conclusion drawing, with data collection techniques through interviews, observation and documentation. The study results indicate that madrasas have implemented educational planning as an initial step in achieving a goal. Islamic education planning at MA Nurul Muhajirin includes long-term planning because several programs are planned and conceptualized in the annual program of the madrasa related to the vision and mission in detail. Furthermore, Islamic education planning is also integrated with programs related to empowering students to have competence in cognitive but also affective and psychomotor aspects. All of these activities are integrated into education management. Finally, in planning education in Madrasas, it is not only the quantity aspect of the institution but also the quality aspect that is quite important.